Linguistic purism and language criticism in European perspective - Große, Sybille (Handbuch europäische Sprachkritik online, 2018)
This article examines the postulate of the ‘purity’ of language, which was previously presented for the different language cultures individually, comparatively in diachronic and synchronic perspective, correlating the different traits. ›Linguistic purism‹ is hereby seen as both criticism of language use and criticism of forms and structures of a language. The comparative article illustrates in which constellations of languages linguistic purism was relevant in the past and still is today and how the individual languages were and are affected by language-puristic activities. Finally, the article will compare the actors and specific discursive connections between the different language cultures.
Gesehen am 06.07.2020